Long-Term Outcomes in Children with Steroid-Resistant Nephrotic Syndrome Treated with Calcineurin Inhibitors - Beins, Nathan T.; Dell, Katherine M. (Frontiers in Pediatrics, 2015)
Background Steroid-resistant nephrotic syndrome (SRNS) is an important cause of chronic kidney disease (CKD) in children that often progresses to end-stage renal disease (ESRD). Calcineurin inhibitors (CNIs) have been shown to be effective in inducing short-term remission in some patients with SRNS. However, there are little data examining their long-term impact on ESRD progression rates. Methods We performed a retrospective chart review of all patients treated for SRNS with CNIs at our institution from 1995 to 2013. Data collected including demographics, initial response to medical therapy, number of relapses, progression to ESRD, and treatment complications. Results A total of 16 patients met inclusion criteria with a mean follow-up of 6.6 years (range 0.6–17.6 years). Histopathological diagnoses were focal segmental glomerulosclerosis (8), mesangial proliferative glomerulonephritis (4), IgM nephropathy (3), and minimal change disease (1). Three patients (18.8%) were unresponsive to CNIs while the remaining 13 (81.2%) achieved remission with CNI therapy. Six patients (37.5%) progressed to ESRD during the study period, three of whom did so after initially responding to CNI therapy. Renal survival rates were 87, 71, and 57% at 2, 5, and 10 years, respectively. Non-Caucasian ethnicity was associated with progression to ESRD. Finally, a higher number of acute kidney injury (AKI) episodes were associated with a lower final estimated glomerular filtration rate. Discussion Despite the majority of SRNS patients initially responding to CNI therapy, a significant percentage still progressed to ESRD despite achieving short-term remission. Recurrent episodes of AKI may be associated with progression of CKD in patients with SRNS.